(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In this paper we present about Shakespeare’s demonstration of women inhis tragedies. Titus converts into a temperament of carnival in Shakespeare’s“Titus Andronicus.” Carnivals behavior includes using disguises, being creativeand ridiculing power. The culture is associated with “grotesque” humor thatcombines the funny and horrifying, usually with issues related to death. Titusis far from a typical carnivals character at the beginning of the play.